2020
DOI: 10.1002/asl.956
|View full text |Cite
|
Sign up to set email alerts
|

Monthly variation and spatial distribution of quadrant tropical cyclone size in the Western North Pacific

Abstract: With the tropical cyclone (TC) size parameter defined as the radius of 17-mÁs −1 oceanic surface wind, 225 TC cases were recorded in the western North Pacific during 2000-2009 based on the QuikSCAT near-surface wind vector database and the best-track dataset. In accordance with the symmetry index (the ratio of minimum and maximum quadrant sizes), the TCs were classified into symmetric and asymmetric structures. The asymmetric TCs were divided into four types: the northeast, southeast, southwest, and northwest.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Finally, it made landfall in SK. The model performance of typhoon track simulation is important to reproduce the structure of typhoon surface precipitation and cloud hydrometeors(Merrill 1984, Irish et al 2008, Chavas and Emanuel 2010, Hong et al 2020, Kumar et al 2020. Besides the well-simulated precipitation by WRF, the typhoon track was also consistent with that obtained from Japan Meteorological Agency (Text S3 and figureS4).…”
supporting
confidence: 68%
“…Finally, it made landfall in SK. The model performance of typhoon track simulation is important to reproduce the structure of typhoon surface precipitation and cloud hydrometeors(Merrill 1984, Irish et al 2008, Chavas and Emanuel 2010, Hong et al 2020, Kumar et al 2020. Besides the well-simulated precipitation by WRF, the typhoon track was also consistent with that obtained from Japan Meteorological Agency (Text S3 and figureS4).…”
supporting
confidence: 68%
“…In addition, the TCs in west of 140 E and north of 15 N are more symmetric than those elsewhere, which are different from other months. Hong et al (2020) also found that most of the symmetric TCs were located in similar region.…”
Section: Spatiotemporal Variationsmentioning
confidence: 73%
“…In addition, Zhao et al (2019) suggested that the rate of change of azimuthal tangential wind are sensitive to the TC location and moving direction, which lead to inaccurate asymmetric decomposition. Hong et al (2020Hong et al ( ) studied a 10-year climatology (2000Hong et al ( -2009 of TC size asymmetry in the western North Pacific using the QuikSCAT satellite data and found that the lifetime, motion, and location of TCs can lead to different asymmetric structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation